Design of BIPA Teaching Materials in the Riau Islands Context for Darmasiswa Students - Marsevani, Maya; Bal Jannate Raj Kaur; Gabriela Micheline Slikker; Jennifer Wiwit; Desty Febria (Journal of Education Reseach and Evaluation, 2024)
Indonesian for Foreign Speakers (BIPA) is Indonesian for Foreign Speakers (BIPA) is a learning program to help foreign students learn Indonesian and familiarize themselves with its culture. This study aims to design an Indonesian language learning book for Foreign Speakers (BIPA) by highlighting the culture of the Riau Islands at a university in Batam using audio-visual aids, especially for Darmasiswa Republic of Indonesia students. The aim of this research is to design Indonesian language teaching materials for Foreign Speakers (BIPA) that focus on the cultural context and local wisdom of the Riau Islands, especially for Darmasiswa program students. This research found that it is critical to include interactive and culturally relevant resources in BIPA training, using research and development (RnD) methodology using interviews as the instrument. There were 6 Darmasiswa students who were interested in learning Indonesian who were the subjects of the research. In collecting the data, interviews were conducted and to analyze the data the researchers transcribed the data that had been obtained. The results of this research shed new light on the process used to create BIPA teaching material books that can be used for learning for foreign students at the Riau Islands level. This shows that making BIPA textbooks interactive with audiovisual components and adding interactive sections can increase student interest and participation. BIPA learning can be brought closer to the goals and ability levels of students by practicing efficient strategies to overcome discovered deficiencies and redesigning learning materials to increase interaction, diversity and cultural relevance. The implication of this research is that providing BIPA teaching materials designed with the context of the Riau Islands can provide significant benefits for the learning of Indonesian language and culture by Darmasiswa students.